The Relation between Fatigue and Self-management in Patient with Diabetes Melitus Type 2 in Dr Soebandi Hospital Jember - Yazid, Syahrul Abdul; Sutawardana, Jon Hafan; Siswoyo, Siswoyo (University of Muhammadiyah Malang, 2020)
Introduction: Fatigue that felt by diabetes melitus patient will be a barrier when doing self-management. An ineffectiveness of self-management will affect many complications, either macrovascular and microvascular. Objective: The goal of this research is determine the relation of fatigue and self-management of diabetes melitus type 2. Method: The design of this research is using observative correlative with cross – sectional way. There are 102 research samples obtained from the calculation G*Power. The methode of taking the data doing with way to gather use with Multidemensional Fatigue Inventory (MFI20) questionnaire and Diabetes Self-Management (DSMQ) that has tested validity and realibility for analyze the fatigue and self-management. The data from analyzed using spearman rank (α = 0,05). Results: Research’s result average of respondent showed that general fatigue (15,66), physical fatigue (13,8), reduced activity (12,44), reduced motivation (11,01), mental fatigue (11,37). Patient self-management showed if from 102 respondent in majority has good self-management 86 (84.3%) dan 15 (14,7%) the rest of respondent has enough – good. The second analyzed test showed that no relation that significant between fatigue and self-management. Discussion: There are other factor can influence self-management such as, social support and family support. Analyzed test showed if have corelation between reduce activity with managemen glukosa